Early-life Exposure to the SSRI Paroxetine Exacerbates Depression-like Behavior in Anxiety/Depression-prone rats - Glover, Matthew E. (Neuroscience, 2014)
Selective serotonin reuptake inhibitor (SSRI) antidepressants are the mainstay treatment for the 10–20% of pregnant and postpartum women who suffer major depression, but the effects of SSRIs on their children’s developing brain and later emotional health are poorly understood. SSRI use during pregnancy can elicit antidepressant withdrawal in newborns and increase toddlers’ anxiety and social avoidance. In rodents, perinatal SSRI exposure increases adult depression- and anxiety-like behavior, although certain individuals are more vulnerable to these effects than others. Our study establishes a rodent model of individual differences in susceptibility to perinatal SSRI exposure, utilizing selectively-bred Low Responder (bLR) and High Responder (bHR) rats that were previously bred for high versus low behavioral response to novelty. Pregnant bHR/bLR females were chronically treated with the SSRI paroxetine (10 mg/kg/day p.o.) to examine its effects on offspring’s emotional behavior and gene expression in the developing brain. Paroxetine treatment had minimal effect on bHR/bLR dams’ pregnancy outcomes or maternal behavior. We found that bLR offspring, naturally prone to an inhibited/anxious temperament, were susceptible to behavioral abnormalities associated with perinatal SSRI exposure (which exacerbated their Forced Swim test immobility), while high risk-taking bHR offspring were resistant. Microarray studies revealed robust perinatal SSRI-induced gene expression changes in the developing bLR hippocampus and amygdala (postnatal days 7–21), including transcripts involved in neurogenesis, synaptic vesicle components, and energy metabolism. These results highlight the bLR/bHR model as a useful tool to explore the neurobiology of individual differences in susceptibility to perinatal SSRI exposure.